Pengaruh Celebrity Endorser Nadira Alaydrus Terhadap Keputusan Pembelian Luxcrime - Nadhya Salwa Nur Arraafi’a; Velda Ardia (STIKes Ibnu Sina Ajibarang, 2024)
Celebrity Endorser is an advertising star who is expected to be able to promote a product so that consumers are interested. The use of celebrities as endorsers is expected to attract the attention of consumers and influence their purchasing decision-making process for a product. The purpose of this study 1). knowing celebrity endorser Nadira Alaydrus on Luxcrime cosmetic products, 2). knowing consumer purchasing decisions on Luxcrime cosmetic products, 3). measures how much influence celebrity endorser Nadira Alaydrus has on Luxcrime purchase decisions. The approach in research is survey. The collection technique was carried out to 84 respondents on the followers of the Instagram account @luxcrime_id. Sampling method using probalilty sampling technique. The method of taking the questionnaire used is random sampling. The results of this study showed that Celebrity Endorser Nadira Alaydrus influences the decision to purchase Luxcrime.